‘It benefits every moment’: Understandings of and engagements in science-related practices in everyday life - Torkkeli, Kaisa; Karvonen, Milla; Pritup, Daria; Enqvist, Johanna Eeva (Sage PUBLICATIONS, 2025)
Drawing from science capital research and applying current practice theory, this study sheds light on people’s perceptions of science and science-related practices in their everyday lives. The study develops a practice theoretical approach to examine understandings and engagements embedded in socially shared everyday science-related practices. The analysis of 51 interviews with Finnish people aged 20 to 88 with varied educational and socio-economic backgrounds brings participants’ voices into a discussion. The findings suggest that science is understood as a generally valuable all-compassing phenomenon offering a means to explain the world and address complex issues. Participants commonly reported engaging with science in their professional lives, regardless of their educational background or employment status. However, most interviewees implied a lack of confidence to engage in science due to the perceived norms of institutionalised science. This study reveals the need for more critical reflection on the approaches of science-promoting practitioners to advance science engagement.